Online Gender-Based Violence Among Adolescents In Kediri City - Eko Winarti; Yeni Lufiana Novita Agnes; Indah Jayani; Irvan Maulana; Aim Matun Nadhiroh (Universitas STRADA Indonesia, 2025)
This study investigates the incidence, forms, and psychological impacts of Online Gender-Based Violence (OGBV) among adolescents in Kediri City. Employing a quantitative descriptive design, data were collected via online questionnaires from 363 respondents aged 10–19 years in August 2024. Results indicate that 28% of adolescents have encountered gender-based violence online, with 52.9% aware of perpetrators, often friends or acquaintances. Sexual threats, disparaging remarks, and sharing content without consent are the most prevalent types. Because social media use is so common among teenagers, the findings show how exposed they are to OGBV, underscoring the need for strong policy frameworks and focused digital safety education.